A person’s quality of life and features of its measurement - Chykhantsova, Olena Anatoliivna (Insight: the psychological dimensions of society, 2020)
The article conveys the results of a practical evaluationof the methods of psychodiagnostics (n=117) underthe framework of studying a person’s quality of lifeby applying the author’s questionnaire. The purpose of the research is to examine the value of the assessmentof quality of life for its further use and specify the levelof human quality of life as a psychological category. Research methods: the author’s questionnaire, standardizedtests, correlation analysis, descriptive statistics. Results. It is presented the author’s model of qualityof life which is based on the idea that the actual valueof quality of life is reflected in the subjective feelingsof an individual, and these feelings are developed throughthe prism of specific objective conditions. The articleidentifies the psychological features and indices whichclarify the parameters of manifestation of the qualityof life. It is introduced the standardization of the author’smethod “Person’s Quality of Life Questionnaire”, whichconsists of 16 statements, and presented the resultsof a practical evaluation of the method. The distributionof the levels of quality of life has the following points:a low level of quality of life – 16-56 points, an averagelevel of quality of life – 57-58 points, a high level of qualityof life – 86-112 points. The measurement of quality of life is grounded on a person’s assessment of his or herphysical, mental, social and economic well-being. Thereliability of the methods of studying the person’s qualityof life is high (α = .802). The author’s method is investigativeand thus, doesn’t estimate the degree of manifestationof the measured parameters, their standardizing. However,it allows defining the descriptive, qualitative, quantitativecharacteristics of the features under study. A positiveinterrelation between the indicators of the qualityof life and hardiness (=.736; p≤.01), satisfaction with life(=.707; p≤.01), subjective happiness (=.659; p≤.01)and self-efficacy (=.629; p≤.05) is found out. Conclusions. It has been determined such constituents of a person’squality of life as subjective and objective and highlighteda particular significance of the very subjective assessmentof the quality of life for the mental health of an individual.
Keywords: quality of life assessment, satisfaction with life, hardiness